Education in crisis a reference handbook - Gouwens, Judith A. (Santa Barbara, California ABC-CLIO, 2009)
Covers education reform in the United States since the 1950s, focusing on the current condition of American schools and efforts to increase both educational opportunity and overall excellence.
Background and history -- Problems, controversies, and solutions -- Education reform--a global enterprise -- Chronology -- Biographical sketches -- Data and documents -- Directory of organizations -- Resources.
Description based on print version record.
Keywords: Education -- Handbooks, manuals, etc; Education -- United States -- Handbooks, manuals, etc; Electronic books